Efektivitas Manajemen Konflik Dalam Mengatasi Masalah Pada Pt. Pegadaian (Persero) Cabang Tembung (Analisis Manajemen Syariah) - Sy Haura Munawwarah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
If anyone wants to borrow money at the Tembung Branch Pawnshop, you can borrow enough to bring personal items and hand them over at the appraisal counter. At the valuation desk, officers appraise the goods and receive information about the safety value of the goods. However, this often creates a conflict between the valuation wishes of the Pegada owner and the debtor. The conflict management system implemented by Islamic pawnshops is a personal emotional approach between employees and customers in the form of guidance and confirmation about the rules that apply to Islamic pawnshops.